Caracterización molecular con microsatélites aleatorios rams de la colección de mora, rubus spp, de la universidad nacional de colombia sede palmira (2005)
Se estudiaron 36 accesiones, 31 de Rubus glaucus, 3 de R. urticifolius y 2 de R. robustus, mediante marcadores Microsatélites Aleatorios RAMs. Los seis cebadores produjeron 43 bandas polimórficas con pesos moleculares entre 260 y 1500 Kb. El análisis RAMs a un nivel de similitud del 55% diferenció la población en seis grupos de acuerdo con la especie, y relacionó el origen geográfico de R. glaucus e identificó materiales similares de R. robustus. Se encontró un valor de 0.40 de similitud entre materiales silvestres de R. urticifolius y los de R. glaucus; R. robustus presentó el nivel más bajo de similitud 0.25. Según el agrupamiento de las accesiones de acuerdo con el sitio de colecta, el corregimiento de Juntas, vereda La Cecilia (Valle del Cauca), exhibió amplia diversidad y variación entre individuos dentro de las procedencias. ABSTRACT Molecular characterization with random microsatellites rams of the collection of Rubus spp, of the national university of Colombia- Palmira. 36 accesions were studied, 31 belong to the Rubus glaucus species, 3 at R. urticifolius and 2 to R. robustus, by means of markers Random Microsatellite RAMs. The six primers produced 43 polymorphics bands with molecular weights between 260 and 1500 Kb. The RAMs analysis allowed at a level of similarity of 55% differentiating the population in six groups agree with the specie, and to relate the geographical origin of R. glaucus in the group in which they are, and it also identified materials of R. robustus very similar inside the collection. It was a value of 0.40 of similar between the wild materials of R. urticifolius and those belonging to the species R. glaucus, as long as the species R. robustus presented the lowest level in similarity 0.25. The clusters with the collection place suggests that Juntas, Cecilia (Valle del Cauca) it is place that exhibits wide diversity, also evidencing variation among individuals inside the origins. Key words: Rubus glaucus, R. urticifolius, R. robustus, biodiversity, genetic markers, RAMs.